Impact of Primary Caesarean Section on Future Pregnancy Outcome at Urban-Based Tertiary Care Centre in Pakistan - Rubina Atta, Shahida Malik, Amreen Khan, Qudsia Bano, Asia Raza, Momenah Maqsood, Rosemina, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Caesarean section (C-section) is one of the most commonly performed obstetric procedures worldwide. While it is often lifesaving, there are concerns about its long-term effects on future pregnancies, particularly the risks of preterm birth, placenta previa, uterine rupture, and infertility. This study investigates the impact of primary caesarean section on future pregnancy outcomes in women at a tertiary care center in Pakistan. Objective: To assess the impact of primary C-section on the outcomes of subsequent pregnancies, including complications like preterm birth, placenta previa, uterine rupture, and infertility. Methodology: A retrospective study was conducted at Gyne Unit ,Bahawal Victoria Hospital Bahawalpur, during from the Period Feb 2023 to November 2023. This study involving 185 women who had undergone a primary C-section at a tertiary care center. The outcomes of their future pregnancies were evaluated, focusing on preterm delivery, placenta previa, uterine rupture, and other complications. Results: Data were collected from 185 patients, with the primary C-section group having a mean age of 29.6 ± 4.5 years, and the other groups showing a range of 29.1 to 30.2 years. The mean gestational age at delivery was also comparable, with the primary C-section group delivering at 37.5 ± 2.0 weeks, and the groups with asthma, diabetes, cystic fibrosis, and epilepsy showing mean gestational ages of 37.8 ± 1.9 weeks, 37.3 ± 2.1 weeks, 37.4 ± 2.0 weeks, and 37.6 ± 2.2 weeks, respectively. No women in any group had a history of a previous C-section. The risk of preterm birth was found to be 30%, with an odds ratio (OR) of 2.5 (95% CI: 1.3 – 4.7), indicating a 2.5-fold increased likelihood of preterm birth compared to women without a prior C-section. Placenta previa was observed in 15% of women, with an odds ratio of 2.3 (95% CI: 1.1 – 4.6), signifying a 2.3-fold increased risk of this condition in subsequent pregnancies following a primary C-section. Conclusion: Primary caesarean sections significantly impact future pregnancy outcomes. This study emphasizes the need for comprehensive counseling and careful management of pregnancies following a C-section, to mitigate the associated risks. Keywords: Primary caesarean section, future pregnancy outcomes, preterm birth, placenta previa, uterine rupture, infertility, Pakistan.